Gambaran Karakteristik Pasien Infeksi Saluran Pernafasan Akut Yang Menggunakan Antibiotik Di Puskesmas Pekauman Kota Banjarmasin - Nazhipah Isnani; Muliyani Muliyani; Ira Maya Sari (Politeknik Unggulan Kalimantan, 2021)
Acute Respiratory Infection is the lead of infectious morbidity and mortality in the world begins with fever, flu, coughing. In Pekauman Health Center, 482 patients with ARI recorded in April 2019. 83 of them were sampled. This research points to know characteristics and level of knowledge of ARI patients to antibiotics. The research used a qualitative descriptive. Primary data is direct interview with a structured questionnaire. Based on the research, the characteristics of patients were mostly women (61.73%), age 36-45 years (31.33%), Junior High School (46.98%) and housewife (59.03%). Keywords : Acute Respiratory Tract Infection, antibiotics, characteristics of patients